Assimetria de informação em redes de empresas horizontais: um estudo das diferentes percepções de seus atores - Venturini, Jonas Cardona (2008)
The networks interorganizacionais are emerging in different types of organizations that shall see cooperation in an important way to increase competitiveness through the sharing of information, technology, resources, opportunities and risks. This also increases the interest in earnings from this relationship. These gains may be from the asymmetry of information between agents. The main objective of this thesis was to examine how we run this process of informational asymmetry in the horizontal networks in view of its various "stakeholders" (actors members of the networks, without members of management positions; actors presidents and actors consultants). To achieve the proposed objective, the search is worth the method multicasos with nature of exploratory research. Since the main results indicate the presence of an asymmetry of information in networks surveyed, however, gains are still relatively good for its members, which leads to not giving due attention to this process in their networks. Variables of governance, information asymmetry of endogenous and exogenous are present in the speeches of the actors involved in the search.